Radiosensitivity and Seedling Growth of Several Genotypes of Paddy Rice Mutants Irradiated with Gamma Rays at Different Doses - Suliartini, Ni Wayan Sri; Wangiyana, W.; Aryana, I.G.P.M.; Sudharmawan, A.A.K. (International journal of Horticulture, Agriculture and Food science, 2020)
Researchers use mutation induction in rice to create high genetic diversity. The basic population with high genetic diversity will facilitate the selection process for the desired good characters. This study aimed to determine the optimal dose that induces the highest genetic diversity in four lowland rice genotypes. The research materials were four genotypes of lowland rice, namely “G10”, “G16”, “Baas Selem”, and “Inpago Unram-1”. Gamma irradiation was carried out at the Center for Isotope and Radiation Application (PAIR) BATAN. Each genotype was irradiated at doses of 200, 300, 400 and 500 Gy. The seeding is done in the glasshouse of the Faculty of Agriculture, University of Mataram. Observations were made on the number of growing seeds, plant height and number of leaves. The LD50 value was determined based on the results of the regression analysis of the number of growing seeds at the four irradiation doses plus control (0 Gy). The results indicated that (1) the numbers of growing seeds decreased as the doses of gamma irradiation increased, (2) the LD50 value of the four rice genotypes ranged from 264 to 518 Gy, (3) the optimal dose of gamma ray irradiation for G10, G16, Baas Selem, and Inpago Unram-1 were 264 Gy, 398 Gy, 316 Gy and 518 Gy, respectively. (4) Among the four rice genotypes teasted, “G10” mutant was the most sensitive to gamma ray irradiation, whereas” Inpago Unram-1” mutant was the least sensitive genotype.